Reconstruction of Machined Surfaces by Contact Welding and Milling of Worn Parts (Eurasian Scientific Herald, 2022)
Information is provided on the mechanical processing methods used in the preparation or finishing of worn surfaces in mechanical engineering, as well as in the restoration of parts to size or with the installation of additional elements. When the welded surfaces are made by contact welding, sizing and milling, the geometric shape of the working surfaces is restored, and when installing additional elements, its size is adjusted to the size of the new part